A Sociological Approach to Aguk Irawan M.N.’s Novel Senandung Bisu: Social, Moral, Economic, and Religious Dimensions - Siti Anisah Sri Wulandari Sukisno (Yayasan Darussalam Bengkulu, 2025)
This study investigates the role of Senandung Bisu in reflecting the socio-political realities of post-New Order Indonesia, employing Dilthey's hermeneutic triad as a framework to interpret the text. The research utilizes qualitative methods to explore the poem's themes, focusing on its moral, social, and political implications within Indonesian cultural discourse. By analyzing Senandung Bisu as both a literary work and a socio-political commentary, the study examines how language and poetic form interact to shape collective memory and identity in Indonesia. Findings suggest that the poem functions as a powerful tool for critiquing societal issues while simultaneously offering a platform for political engagement and resistance. This study contributes to literary hermeneutics by demonstrating the applicability of hermeneutic analysis to Arabic poetry, bridging the gap between philology, history, and cultural studies. The implications of this research extend to the teaching of Arabic literature, suggesting that the integration of hermeneutic frameworks can foster deeper engagement with literary texts and their cultural significance in educational settings. Future studies should expand this analysis to other literary works from the same era, using comparative methods to enrich the understanding of Indonesian literary heritage.